349 Relationship between ruminal volatile fatty acids and microbial population with carcass and meat quality traits in beef steers. (7th December 2018) - Bulumulla, P; Li, M; Chen, Y; Li, F; White, R; Hanigan, M; Li, C; Plastow, G; Guan, L
Abstract: Volatile fatty acids (VFAs), the end products of rumen fermentation, are the principal energy source for ruminants which potentially affect carcass yield and fat deposition in beef cattle. Rumen microbiota affects lipid metabolism in ruminants which might contribute to the variation in fat deposition. In this study, rumen fluid samples were collected from 204 beef steers raised under feedlot in Roy Berg Kinsella Research Ranch, University of Alberta. Individual VFA concentrations were measured using gas chromatography, and the bacterial and archaeal abundances were estimated by measuring total copy numbers of their respective 16S rRNA genes using qPCR. Animal phenotypic measures including body weight (BW), dry matter intake (DMI), average daily gain (ADG), hot carcass weight (HCW), age at slaughter (age), ribeye area (CREA), adipose fat thickness (AFAT), lean meat yield (LMY) and marbling score (MS) were collected. The relationships among microbiota, VFAs and carcass traits were evaluated using stepwise, backward linear regression with a significant level of 0.05. The HCW was positively correlated with BW and ADG and was negatively correlated with propionate. Negative correlations were identified between age and BW, RFI, acetate, propionate, and butyrate. CREA had positive correlations with BW and DMI, and negative correlations with acetate. AFAT was positively correlated with DMI, BW and propionate while, acetate and butyrate tentatively positively correlated (P < 0.1) with AFAT. The LMY was negatively correlated with BW, DMI, acetate, propionate and butyrate. Marbling score was positively correlated with DMI, acetate, propionate and butyrate. The relationship between rumen microbial abundance and the above carcass and meat quality-related traits were not detected in this study. Our preliminary results reveal that rumen VFAs may contribute to carcass and meat quality traits in beef cattle, suggesting the potential application to improving carcass and meat quality in beef steers through manipulating rumen VFA.